Physical and Psychological Consequences of Left Cardiac Sympathetic Denervation in Long-QT Syndrome and Catecholaminergic Polymorphic Ventricular Tachycardia. (October 2015) - Waddell-Smith, Kathryn E.; Ertresvaag, Kjetil N.; Li, Jian; Chaudhuri, Krish; Crawford, Jackie R.; Hamill, James K.; Haydock, David; Skinner, Jonathan R.
Abstract : Background—: Left cardiac sympathetic denervation reduces risk in long-QT syndrome (LQTS) and catecholaminergic polymorphic ventricular tachycardia. Side effects and patient satisfaction have not been systematically analyzed in patients who underwent left cardiac sympathetic denervation. Aims of this study included documenting physical and psychological consequences and patient satisfaction after left cardiac sympathetic denervation in LQTS or catecholaminergic polymorphic ventricular tachycardia. Methods and Results—: Patients with LQTS (N=40) and catecholaminergic polymorphic ventricular tachycardia (N=7) underwent video-assisted thoracoscopic left cardiac sympathetic denervation, with a median follow-up of 29 months (range, 1–67 months). Clinical records were reviewed; 44 patients completed a telephone survey. Of 47 patients (53%), 25 were preoperatively symptomatic (15 syncope, 7 near-drowning, and 3 resuscitated sudden death). Indications for left cardiac sympathetic denervation included β-blocker intolerance (15; 32%) or nonadherence (10; 21%) and disease factors (18; 38%; catecholaminergic polymorphic ventricular tachycardia [6], near-drowning [2], exertional syncope [1], symptoms on therapy [2], LQT3 [1], QTc>520 ms [6]). Other indications were competitive sports participation (2), family history of sudden death (1), and other (1). Median QTc did not change among patients with LQTS (461±60 to 476±54 ms; P =0.49). Side effects were reported by 42 of 44 (95%). Twenty-nine patients (66%) reported dryness on left side, 26 (59%) a Harlequin-type (unilateral) facial flush, 24 (55%) contralateral hyperhidrosis, 17 (39%) differential hand temperatures, 5 (11%) permanent and 4 (9%) transient ptosis, 5 (11%) thermoregulation difficulties, 4 (9%) a sensation of left arm paresthesia, and 3 (7%) sympathetic flight/fright response loss. Majority of the patients were satisfied postoperatively: 38 (86%) were happy with the procedure, 33 (75%) felt safer, 40 (91%) recommended the procedure to others, and 40 (91%) felt happy with their scar appearance. Conclusions—: Despite significant morbidity resulting from left cardiac sympathetic denervation, patients with LQTS and CPVT have high levels of postoperative satisfaction. Abstract : Supplemental Digital Content is available in the text.